2020
DOI: 10.1061/(asce)hy.1943-7900.0001773
|View full text |Cite
|
Sign up to set email alerts
|

Expulsion of Entrapped Air in a Rapidly Filling Horizontal Pipe

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…The results confirm those obtained in the laboratory by tests on pipes with small diameters and short lengths (L. Zhou et al., 2020), that is, a critical downstream valve diameter, which in the used configuration corresponds to 1/2”, causes the largest overpressure in the system.…”
Section: Downstream Valve Dimensionssupporting
confidence: 88%
See 2 more Smart Citations
“…The results confirm those obtained in the laboratory by tests on pipes with small diameters and short lengths (L. Zhou et al., 2020), that is, a critical downstream valve diameter, which in the used configuration corresponds to 1/2”, causes the largest overpressure in the system.…”
Section: Downstream Valve Dimensionssupporting
confidence: 88%
“…All the other cases between the two limiting cases, with a downstream open valve smaller than the pipe diameter and not fully closed, are expected to cause different pressure variations during the filling depending on the size of the downstream valve (F. Zhou et al., 2002b; L. Zhou & Liu, 2013; L. Zhou et al., 2020).…”
Section: Downstream Valve Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of orifice size on pressure surge during air expulsion. Figures (14)(15)(16)(17) illustrate pressure oscillation as a result of air expulsion from four different orifices sizes (d0=1.5-3-5-7 mm). The location (P3) was selected using fixed value of air pocket (Lao3=50cm) in the four cases (Lao3=50 cm, do=7 mm).…”
Section: 41mentioning
confidence: 99%
“…His results concluded that for larger orifices higher pressure surge is recorded with short descending slop. Zhou, Cao, Karney, Bergant, Tijsseling, Liu and Wang [16] have introduced an experimental and analytical investigation for air expulsion through horizontal end piped orifice. Details of air water pattern are investigated using image processing technique to identify the type of released flow whether its air, mist, water with little air or pure water with air volume variations and different orifice flow regimes.…”
Section: Introductionmentioning
confidence: 99%